Role Play Therapy to Improve Socialization Ability in Social Isolation Patients in Danasari Health Center Area, Tegal Regency - Ramadhan Putra Satria; Syahvena Restika Putri (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Social isolation is a condition when a person experiences decreased social functioning due to negative thoughts, unpleasant experiences that threaten them. Patients who experience social isolation will have difficulty interacting, show behavior that does not want to interact with others, prefer to stay silent, and avoid other people. So it is necessary to use role-playing training techniques to improve the ability to socialize. This study aims to implement role-playing therapy to improve socialization skills in social isolation patients. The design used by researchers is a descriptive case study. The case study subjects in this study were 2 patients who experienced social isolation disorder by applying role-playing therapy for 3 days. Data obtained from interviews, observations, documentation and presented in narrative form. The results of the application of therapy for 3 days increased the ability to socialize. Namely in patient 1 before therapy the results were 55 points with Yes (3) No (3) after therapy became 85 points with Yes (5) No (1). While in patient 2 the ability to socialize before therapy the results were 35 points with Yes (2) No (4) after therapy to 70 points with Yes (4) No (2). Patients with social isolation disorders are given the application of role-playing therapy, namely 1 time a day for 45 minutes to improve socialization skills in social isolation patients